1985
DOI: 10.1128/mcb.5.6.1287
|View full text |Cite
|
Sign up to set email alerts
|

Localization of specific rDNA spacer sequences to the mouse L-cell nucleolar matrix.

Abstract: Mouse L-cell nucleoli were isolated from sonicated nuclei by centrifugation and extensively treated with pancreatic DNase or micrococcal nuclease to obtain "core nucleoli." Core nucleoli still contained the precursors to rRNA and about 1% of the total nuclear DNA, which remained tightly bound even after the removal of some chromatin proteins with 2 M NaCl. The core nucleolar DNA electrophoresed in a series of discrete bands, 20 to about 200 base pairs in length. Hybridization tests with specific DNA probes sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…At one extreme, the nucleolus might be essential to provide a requisite concentration or spatial arrangement of factors for rDNA transcription, rRNA processing, and ribosome assembly; at the other extreme, the nucleolus might form quite passively and merely reflect an aggregation of ribosomal precursors. Further study, presumably in part involv ing cloned rDNA that has been reintroduced into cells (233), will be needed to resolve these issues.…”
mentioning
confidence: 95%
“…At one extreme, the nucleolus might be essential to provide a requisite concentration or spatial arrangement of factors for rDNA transcription, rRNA processing, and ribosome assembly; at the other extreme, the nucleolus might form quite passively and merely reflect an aggregation of ribosomal precursors. Further study, presumably in part involv ing cloned rDNA that has been reintroduced into cells (233), will be needed to resolve these issues.…”
mentioning
confidence: 95%
“…We have previously shown that certain rDNA regions are protected against exhaustive treatment of nucleoli with DNase I or micrococcal nuclease (5). Fig.…”
Section: Resultsmentioning
confidence: 91%
“…At present, we have no idea whether the poly(dGdC)-poly(dG-dC) or poly(dG-dT)-poly(dA-dC) tracts are ever found in a Z-DNA conformation in vivo; but an association of such nontranscribed sequences at the base of the looped-out transcription unit with proteins (that give selective protection against DNase I) may effect the relative increased exposure of the transcribed sequences and account for their sensitivity to DNase I action (5). Such an organizational role of spacer DNAs could provide a basis for the observations that some sequences within spacers (15), including certain poly(dGdT)-poly(dA-dC) sequences (16) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding these questions, seemingly contradictory models were proposed: Keppel suggested that the entire rDNA repeat unit is associated with the nuclear matrix (34), whereas others found that the coding sequence itself (35) or non-transcribed regions flanking the 47S rRNA coding sequence are predominantly enriched in the nuclear or nucleolar matrix (36–38). With regard to the transcriptional activity of nuclear matrix-associated DNA, it was suggested on one side that active rDNA is associated with the nuclear matrix (34,36), and on the other side that the nuclear matrix contains transcriptionally inactive rDNA (38), which could also represent sequences that are being replicated (39). These discrepancies can be explained largely by differently used terminology and differences in the experimental procedures.…”
Section: Discussionmentioning
confidence: 99%